Theological analysis of women’s roles in black reformed churches of Soutpansberg - Mudau, Ndidzulafhi; Khosa-Nkatini, Hundzukani P. (Hervormde teologiese studies, 2025)
The prohibition on women leading worship services and serving as elders, deacons and reverends in many black reformed churches in the Synod Soutpansberg remains a major concern. Adherence to traditional gender standards not only perpetuates gender disparities but also limits women’s full participation and contributions inside the church. It is critical to address this issue in order to foster a more inclusive and egalitarian church culture. This scholarly inquiry tries to call into question the existing restrictions and redefine the roles given to genders within these religions by looking at the theological, cultural, and historical roots that support these gender-based exclusions. The inspiration for this research stems from the need to align church activities with current ideas about gender equality and justice. This study seeks to empower women and improve the spiritual and communal life of the church by thoroughly examining present gender roles and proposing alternative frameworks for inclusion, such as allowing women to lead worship services and serve as elders, deacons and reverends. The study employed a literary study, which comprised a thorough review of existing literature on gender roles in religious settings. This entailed examining church documents that define contemporary practices and beliefs, and theological writings that provide theological support for these practices.ContributionThis study has enormous implications as it has the ability to influence the gender dynamics in the black reformed churches of the Synod Soutpansberg. This work contributes significantly to the field of gender studies in religion by challenging established boundaries and pushing for more inclusive practices.